2018
DOI: 10.1038/s41409-018-0261-y
|View full text |Cite
|
Sign up to set email alerts
|

Final outcomes of escalated melphalan 280 mg/m2 with amifostine cytoprotection followed autologous hematopoietic stem cell transplantation for multiple myeloma: high CR and VGPR rates do not translate into improved survival

Abstract: The most common preparative regimen for autologous transplantation (ASCT) in myeloma (MM) consists of melphalan 200 mg/m (MEL 200). Higher doses of melphalan 220-260 mg/m, although relatively well tolerated, have not shown significant improvement in clinical outcomes. Several approaches have been pursued in the past to improve CR rates, including poly-chemotherapy preparative regimens, tandem ASCT, consolidation, and/or maintenance therapy. Since there is a steep dose-response effect for intravenous melphalan,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
0
5
0
2
Order By: Relevance
“…A randomized study comparing conditioning with melphalan 280 to 200 mg/m 2 while receiving amifostine demonstrated significantly higher ORR and nCR without an improvement in OS and PFS in patients receiving melphalan 280 mg/m 2 at the cost of higher incidence of grade 2–3 mucositis and gastrointestinal toxicities 75 . Another study demonstrated similar results with deeper responses on melphalan 280 mg/m 2 without translating into improved survival 76 .…”
Section: What Is the Optimal Conditioning Regimen Prior To Asct?mentioning
confidence: 71%
“…A randomized study comparing conditioning with melphalan 280 to 200 mg/m 2 while receiving amifostine demonstrated significantly higher ORR and nCR without an improvement in OS and PFS in patients receiving melphalan 280 mg/m 2 at the cost of higher incidence of grade 2–3 mucositis and gastrointestinal toxicities 75 . Another study demonstrated similar results with deeper responses on melphalan 280 mg/m 2 without translating into improved survival 76 .…”
Section: What Is the Optimal Conditioning Regimen Prior To Asct?mentioning
confidence: 71%
“…While HDM has been evaluated at 100–300 mg/m 2 , these studies did not obtain PK data, did not test pharmacodynamic or pharmacogenomic markers, and did not incorporate sensitive assays for minimal residual disease. In fact, melphalan 280 mg/m 2 with amifostine protection has been explored in prior studies and although this regimen has been associated with slightly increased toxicities, variability in responses have also been observed, with 1 study demonstrating improved CR rates and another not observing major improvement in PFS with long‐term follow‐up 34,35 . Because of the known wide interpatient variability in melphalan exposure after BSA‐based dosing, it is possible that there were some patients who would have an already expected higher melphalan exposure after melphalan 200 mg/m 2 and upon further dose escalation experienced an even higher AUC and increased toxicities.…”
Section: Discussionmentioning
confidence: 99%
“…Способом преодоления негативного влияния неблагоприятных цитогенетических аберраций может быть увеличение дозы мелфалана, например, до 280 мг/м 2 , вводимого внутривенно однократно в течение 15 мин под прикрытием цитопротективного действия амифостина [33]. Однако показатели 7-летних ВБП и ОВ, составившие 10 % с медианой 22 мес.…”
Section: Discussionunclassified